1986
DOI: 10.1111/j.1432-1033.1986.tb09690.x
|View full text |Cite
|
Sign up to set email alerts
|

Mucin synthesis

Abstract: A UDP-GlcNAc:R,-p1-3Gal(NAc)-R2 [GlcNAc to Gal(NAc)] P6-N-acetylglucosaminyltransferase activity from pig gastric mucosa microsomes catalyzes the formation of GlcNAcfil-3(GlcNAcB1-6)Gal-R from GlcNAcpl-3Gal-R where -R is -jl-3GalNAc-or-benzyl or -~l-3(GlcNAc~l-6)GalNAc-a-benzyl. This enzyme is therefore involved in the synthesis of the I antigenic determinant in mucin-type oligosaccharides. The enzyme also converts Galj1-3Galpl-4Glc to Gal~l-3(GlcNAcfl1-6)Galfll-4Glc. The enzyme was stimulated by Triton X-100 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
22
0

Year Published

1986
1986
2000
2000

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(23 citation statements)
references
References 36 publications
1
22
0
Order By: Relevance
“…These linear and branched poly-N-acetyllactosamines represent, respectively, the i and I antigens, which are expressed in a cell type-specific manner (1). It has been shown that there exist two IGnTs, which use two different sets of acceptor substrates (15)(16)(17).In the gastrointestinal tract, oligosaccharides with core 3, GlcNAc␤133GalNAc, can be frequently found. These tissues also contain core 4, Gal␤134GlcNAc␤136(GlcNAc␤133)GalNAc, which was originally discovered in sheep gastric mucosa (18).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…These linear and branched poly-N-acetyllactosamines represent, respectively, the i and I antigens, which are expressed in a cell type-specific manner (1). It has been shown that there exist two IGnTs, which use two different sets of acceptor substrates (15)(16)(17).In the gastrointestinal tract, oligosaccharides with core 3, GlcNAc␤133GalNAc, can be frequently found. These tissues also contain core 4, Gal␤134GlcNAc␤136(GlcNAc␤133)GalNAc, which was originally discovered in sheep gastric mucosa (18).…”
mentioning
confidence: 99%
“…These linear and branched poly-N-acetyllactosamines represent, respectively, the i and I antigens, which are expressed in a cell type-specific manner (1). It has been shown that there exist two IGnTs, which use two different sets of acceptor substrates (15)(16)(17).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Surprisingly, these two genes were not similar in sequence to GnTV, which is responsible for formation of the ␤6GlcNAc branch in tetraantennary N-linked glycans (23). Studies of the kinetic properties and acceptor substrate specificities of ␤6GlcNAc-transferases involved in O-glycosylation from different cell lines and organs have suggested that multiple ␤6GlcNAc-transferases exist and that one of these would function in a manner that is distinct from the cloned C2GnT enzyme, in being capable of forming core 2, core 4, and possibly the branched I antigen structure (17,18). The existence of a homologous ␤6GlcNAc-transferase family containing C2GnT and IGnT suggests that additional ␤6GlcNAc-transferase activities may be encoded by homologous genes (22).…”
mentioning
confidence: 99%
“…Two candidate branching reactions involving distinct ␤1,6-N-acetylglucosaminyltransferases (IGnT6) have been described in vitro (1). The "distally acting" dIGnT6 transfers a GlcNAc unit in the ␤1,6 linkage to the penultimate galactose residue at the growing end of the linear polylactosamine chain (Scheme 1) (2)(3)(4)(5)(6)(7)(8). By contrast, the "centrally acting" cIGnT6 transfers a GlcNAc residue in the ␤1,6 linkage to midchain galactose units of preformed as well as growing linear chains (3,9,10).…”
mentioning
confidence: 99%